Analgesic and anti-inflammatory activities of the extract of Polypodium feei mett roots - Suwandi, Deden Winda; Renggana, Hesti; Subarnas, Anas; Rostinawati, Tina; Muchtaridi, Muchtaridi; Sadino, Asman (Pharmaciana, 2025)
The limited scientific evidence on the analgesic and anti-inflammatory effects of Polypodium feei roots, despite their traditional use in rheumatism treatment, highlights the need for pharmacological validation. The study investigates the analgesic and anti-inflammatory properties of Polypodium feei roots, a traditional medicine used to treat rheumatism, in mice and rats with carrageenan-induced paw edema, using acetylsalicylic acid and tramadol as analgesics and diclofenac sodium as an anti-inflammatory. The writhing test results demonstrate that the extract of P. feei roots (EPFR) at dosages of 50 and 100 mg/kgBW lowered the writhing responses of rat significantly (p <0.01). The dose of 100 mg/kgBW provided more protection than acetylsalicylic acid at a level of 65 mg/kgBW. In the hot plate method, the extract increased the latency period significantly (p <0.05) as compared with the control. In the anti-inflammatory examination, the EPFR decreased edema of rat paws induced by carrageenan. The significant effect of the EPFR was shown by the dose of 100 mg/kgBW (p <0.05), but its inhibition was lower than that of a standard agent, diclofenac sodium. This study concluded that the EPFR may have peripherally and centrally analgesic activity and anti-inflammatory activity. This evidence supports the folklore claim of the efficacy of EPFR as traditional medicine for rheumatism.